Phenolic compounds from knema pachycarpa leaves - Le Nguyen Thanh,; Tran Huu Giap,; Vu Thi Hue,; Diep Thi Lan Phuong,; Nguyen Thi Hue,; Nguyen Hoang Nam,; Nguyen Quoc Vuong, (Vietnam Journal of Science and Technology, 2023)
Knema (Myristicaceae family) is a large genus, comprising over 100 species found in of South East Asian countries, among that over 10 species was found in Vietnam. Knema pachycarpa is a native tree distributed in central provinces of Viet Nam. Until now, only few chemical studies of Knema species in Viet Nam have been reported. Phytochemical study of Knema pachycarpa leaves led to the isolation of seven known compounds including six flavonoids 5,7,3′-trihydroxy-5′-methoxy isoflavone (1), luteolin (2), (-)-narigenin (3), (+)-catechin (4), isoquercetrin (5), and nicotiflorin (6), and a biphenyl compound  3,3',4,4'-tetrahydroxybiphenyl (7). Their structures were elucidated by MS and NMR data analysis and compared with those previously reported. Compounds 3 and 6-7 were found from Knema genus for the first time. In the cytotoxic assay, biphenyl compound (7) exhibited strong cytotoxicity to KB cancer cell line with IC50 value of 2.38 ± 0.11 mg/mL. Compound 7 also displayed showed activity against HepG2, Lu and MCF7 cancer cell lines with IC50 ranges from 18.25 ± 0.92 mg/mL to 35.56 ± 1.17 mg/mL, whereas flavonoids 1-6 were weakly active or inactive against tested cell lines.